No Man’s Land: Exploring the Space between Gilligan and Kohlberg - Donleavy, Gabriel D. (Journal of business ethics, 2008)
The Kohlberg Gilligan Controversy has received intermittent but inconclusive attention for many years, perhaps reflecting the difficulty of bridging the two positions. This article explores the published evidence for Gilligan’s claims of gender difference, gender identity difference, and role of caring in people’s ethics. It seems that the evidence for pronounced gender differences in ethical attitudes within business is weak, even if gender identity is used instead of physical gender. The main propositions of Care Theory and recent advances in its thinking are discussed. Special focus emerges on the notion of Attachment which seems to be the Care Theory ingredient both most able to survive critical scrutiny and most promising for bridging the divide between the Kohlberg and Gilligan paradigms. The Social Bonding Model and other possible bridge building conceptual structures are introduced. Finally, Max Weber’s division between ethics of conviction and ethics of responsibility provides an overarching perspective both of the gap still to be bridged and the need to keep trying to bridge it.